An integral vision of economic transformation: The relevance of Bernard Lonergan to debates in Canadian Catholic social ethics on the relationship of ethics and economics and the function of profit - O'Leary, Darlene Mary (University of Ottawa (Canada), 2007)
Purpose of the thesis. In this thesis, I investigate the relationship of ethics and economics. I situate this inquiry in the context of conversations in Canadian Catholic social ethics. Further, I illustrate this relationship by focussing on the function of profit in an economy. I am addressing ethics and economics out of my own concern about the systemic social and economic problems that so many people face, nationally and internationally, and that have damaged the natural systems of the planet. The Roman Catholic tradition has a long history of social teaching that has spoken out against economic situations that have degraded human dignity and freedom. In the Canadian context, there is also a significant tradition in the official church, among theologians, and in community-based organizations to respond to economic injustice. In this thesis, I use representatives from these three areas of Canadian Catholic social ethics to situate the conversation on the relationship of ethics and economics, and to show its contributions and its limits. Summary and method. This thesis is situated in the context of Canadian Catholic social ethics. My reason for choosing this conversation to investigate the relationship of ethics and economics is my own identity as a Canadian Catholic woman with a long-standing commitment to social justice. I have chosen to illustrate this discussion by focussing on the function of profit in an economy, as profit has become a symbol in the conflicts about economic justice, symbolizing success to some and greed to others. The conversation partners that I have chosen reflect three significant areas of Canadian Catholic social ethics: the Canadian Catholic bishops represent the "official" church; Gregory Baum represents the voice of critical theology and critical theory; and Moses Coady and the Antigonish Movement represent the concrete community-based social economic approach. I identify the key contributions of these three conversation partners, noting that they offer a strong grounding in the principles of the Catholic social tradition. They share a deep commitment to challenging an economic situation that threatens the dignity and freedom of people. They all point to the importance of the social economy in its community-based, democratic approach to empowering those who suffer economic injustice. A key limit to all three approaches, however, is the lack of a macroeconomic analysis that could provide an alternative to mainstream analyses and could ground ethical imperatives in its very dynamics. In addressing this limit, I turn to the work of Bernard Lonergan. Lonergan offers a macroeconomic analysis that is quite unique in that it challenges the limited single-circuit analyses that ground mainstream economics. Lonergan follows the insights of economists like Joseph Schumpeter and develops a two-circuit analysis, one that distinguishes two distinct circuits of productive activity and circulations of payments. With this distinction, Lonergan sets out the activities, relationships, and dynamic rhythms of an economic order. This analysis accounts for the elements of production and payments, their dynamic flows and fluctuations, and their effects on each other. In light of these relationships, Lonergan's macroeconomic analysis allows for an understanding of the function of profit as a social dividend. Lonergan's macroeconomic analysis is situated in the broader context of his work on the structure of ethics. For Lonergan, there are different meanings of the good that can be distinguished in accordance with increasingly broad horizons of concern: particular goods, goods of order, and value. Economic orders are goods of order that regularly provide particular goods to everyone. As goods of order, they are structures of collaboration and intelligence whose dynamism transcends the narrow limits of self-interest. Goods of order are situated in the broader context of progress, decline, and redemption in history. In this broader context, values function to evaluate whether or not goods of order are performing their tasks of serving the well-being of everyone. While the broader horizon of values can offer challenges and guiding principles to the economic goods of order, they still require the analytical tools to understand how economies can achieve this goal. As the ultimate goal of solving economic problems, Lonergan's methodology of functional specialization is identified as providing a strategy for interdisciplinary collaboration that sets out the relationships of theological doctrinal directives and systematic analytical response. The eight-fold methodology of functional specialization provides a cycle of discovery and response that strategically raises the foundational question of conversions and self-transcendence in searching for solutions to problems of history. In this way, the question of God's loving presence in history becomes part of the cycle of discovery and response. This ultimately places the solution of economic problems in the context of progress, decline, and redemption in history with a broad methodological strategic response. (Abstract shortened by UMI.)
Keywords: Theology.